Implementasi Metaverse Dalam Menciptakan Produk Fashion Design Berbasis Android - Khairunnisa; Graciella Hutahaean; Nenna Irsa Syahputri (SNASTIKOM, 2023)
Fashion has an important role in judging a person based on their appearance and daily style. Fashion, such as clothing and accessories, is growing rapidly in Indonesia with models changing every year. Therefore, the current fashion design process is done digitally using information technology, with the aim of producing good quality and satisfying customers in choosing and making their choices.The application used to design this fashion is Unity, a software that allows the creation of a fashion metaverse in 3D using the Marker Based Method. This method utilizes images as markers to bring up fashion in 3D in existing data. The purpose of this research is to create an Android-based metaverse fashion design application with AR technology that can facilitate a person in determining the desired fashion model by using a smartphone as a search tool. The results showed that most respondents, around 90%, strongly agreed with this application, indicating that this application is very useful in making it easier to select the desired fashion model.